Multielemental composition and nutritional value of "dumosa" (Ilex dumosa), "yerba mate" (I. paraguariensis) and their commercial mixture in different forms of use - Maiocchi, Marcos G. (2016)
The multielement composition and nutritional value of "dumosa" (Ilex dumosa) (ID), "yerba mate" (I. paraguariensis) (IP) and their commercial 70:30 mixture (ID:IP, w/w) in crude drug, brewed mate and tea-bag-like infusion were studied by ICP-OES. This method allowed the detection of an unprecedented number of elements for these species. The order was K>Ca>Mg>P>Mn>Al>Na>Si>Fe in crude drug. IP showed higher concentration of minerals than ID, but most extractability in the latter largely offset its shortcomings. Brewed mate had higher nutritional value than mate tea because their higher solute/solvent ratio. A portion of brewed mate of both species exceeded the daily recommended intake (DRI) of Mn, and providing Mg, Cu, Fe, Zn and K, too. The portions of mate tea not contribute significantly to the DRI. Some essential trace elements and many ultra-traces ones that exist in crude drug were not detected in aqueous extracts. Most of the heavy metals were not leached into extracts, and in any case never exceeded international safety limits. Therefore, the aqueous extracts of ID and IP and its mixture are interesting from the nutritional point of view in minerales, and safe in terms of health.